Dipole doping effect in MoS2 field effect transistors based on phase transition of ferroelectric polymer dopant - Lee, Dong Hyun; Park, Taehyun; Jeong, Taeho; Jung, Youngkyun; Park, Junghee; Joo, Nackyong; Won, Uiyeon; Yoo, Hocheon (Frontiers in Materials, 2023)
Molybdenum disulfide (MoS2) has great potential for next-generation electronic devices. On the other hand, stable doping methods are required to adjust its physical properties so MoS2 can be utilized in practical applications, such as transistors and photodetectors. On the other hand, a conventional doping method based on ion implantation is incompatible with 2D MoS2 because of the damage to the lattice structures of MoS2. This paper presents an n-doping method for MoS2 field-effect transistors (FETs) using a poly(vinylidene fluoride-co-trifluoroethylene) (P(VDF-TrFE)) and polar polymer. The dipole moment of P(VDF-TrFE) provides n-type doping on MoS2 FETs. The polar phase formation in dopant films enhances the doping effects, and the relationship between phase transition and n-doping states was investigated using optical and electrical characterization methods. Under the optimal doping conditions, the doped MoS2 FET achieved an improved field effect mobility of 34.4 cm2/Vs, a negative shift in the threshold voltage by 25.6 V, and a high on-current of 21 μA compared to the pristine MoS2 FET.